PENGARUH FILM LASKAR PELANGI TERHADAP KESADARAN PENDIDIKAN MAHASISWA DI YOGYAKARTA - Hasanah, Alfiani Nur Aqqara; Sinarmata, Monalisa; Sarbiyanti, Wiwik (Lembaga Penelitian dan Penerbitan Hasil Penelitian Ensiklopedia, 2026)
This study aims to examine the influence of the perception of the film Laskar Pelangi on the educational awareness of students in Yogyakarta. Amidst the challenges of character building in higher education, cinema is proposed as an effective medium for value internalization. Employing a quantitative approach with simple linear regression analysis, this study involved 155 respondents selected through purposive sampling techniques. Data collection was conducted using a Likert-scale questionnaire that had been validated and tested for reliability. The results indicated a positive and significant influence between film perception and educational awareness with a significance value of 0.000 (p < 0.05). The coefficient of determination (R^2) revealed that the film Laskar Pelangi contributed 72.5% to the formation of educational awareness, which encompasses motivation, gratitude, and academic responsibility. These findings conclude that inspirational films serve as a powerful instrument in shaping students' psychological perspective toward education.Keywords: Laskar Pelangi Film, Educational Awareness, Social Learning, Cinema Media, Students